Enhanced recognition of emotional images is not affected by post-exposure exercise-induced arousal. Issue 6 (June 2022) - Smith, Veronica M; Watson, Poppy; Most, Steven B
Research suggests that aerobic exercise (i.e., exercise aiming to improve cardiovascular fitness) promotes cognition, but the impact on memory specifically, is unclear. There is some evidence to suggest that as little as one session of post-learning exercise benefits memory consolidation. Furthermore, memory may be particularly facilitated by exercise when the individual is emotionally aroused while encoding stimuli. The current study tested whether exercise after exposure to neutral and emotional images improved memory consolidation of the items among university students. Ninety-nine students were randomly instructed to either exercise or not exercise after viewing a set of images that were positive, neutral, and negative in valence, and they were later tested on their memory. Although emotional images were remembered better than non-emotional images, the results suggested that exercise did not influence this effect or enhance consolidation of the items overall. Explanations and implications for these findings are discussed.